THE EFFECT OF POPULATION DEPENDENCY, TECHNOLOGY, AND EDUCATION ON HUMAN DEVELOPMENT IN INDONESIA DURING THE PANDEMIC COVID-19 - Norma Ayu Wahyuni; Sri Indah Nikensari; Saparuddin Mukhtar (International Journal of Multidisciplinary Research and Literature, 2022)
This study aims to determine the effect of population dependence, technology, and education on human development. Human development in this research is measured by adjusted per capita expenditure. The research method used in this study is from panel data from 2019 – 2021 in 34 provinces in Indonesia with a descriptive quantitative model. Based on the partial analysis, the population dependency technology variable has a positive and significant effect on human development by the probability value of smaller than alpha (0.05). At the same time, the education variable has a negative and significant effect on human development in Indonesia during the covid-19 period. Simultaneously, all variables significantly affect human development, shown through R2 of 99.80% and 0.20% and are explained by other variables outside the study.